发布网友
发布时间:11小时前
共4个回答
热心网友
时间:4分钟前
CuA={x|x≤-2 或3≤x≤4}
A∩B={-2<x≤1}
Cu(A∩B)={x|x≤-2 或1<x≤4}
(CuA)∩B={-3<x<-2}
热心网友
时间:3分钟前
CuA={x|x小于等于-2 并 3小于等于x小于等于4},
A∩B={x|-2<x小于等于1},
Cu(A∩B)={x|1<x小于等于4},
(CuA)∩B={x|-3<x小于等于-2 },
希望采纳,O(∩_∩)O谢谢
热心网友
时间:1分钟前
CuA={x|3≤x≤4或x≤-2};
A∩B={x|-2<x≤1};
Cu(A∩B)={x|1<x≤4或x≤-2};
(CuA)∩B={x|3≤x≤4或x≤-2}∩{x|-3<x≤1}={x|-3<x≤-2} 。
热心网友
时间:8分钟前
CuA = R - A
= R- {x|-2<x<3}
= {x| x ≤ -2 or x≥3}
A∩B = {x|-2<x<3} ∩ ={x|-3<x≤1}
= {x| -2<x≤1}
Cu(A∩B) = R - A∩B
= R - {x| -2<x≤1}
= {x| x≤-2 or x>1}
(CuA)∩B = {x| x ≤ -2 or x≥3} ∩ {x|-3<x≤1}
={x| -3< x≤ -2 }